Factors associated with xerostomia in perimenopausal women. Issue 10 (5th August 2021) - Shinohara, Chizuko; Ito, Kayoko; Takamatsu, Kiyoshi; Ogawa, Mariko; Kajii, Yuka; Nohno, Kaname; Sugano, Aki; Funayama, Saori; Katakura, Akira; Nomura, Takeshi; Inoue, Makoto
Abstract: Objectives: Various oral symptoms, including xerostomia and burning mouth syndrome, may occur in menopausal women. These symptoms reduce quality of life (QOL). However, the actual condition of xerostomia after menopause is not clear. The purpose of this study was to reveal the factors associated with xerostomia in perimenopausal women. Methods: Participants included 118 outpatients (mean age, 49.9 ± 3.2 years; range, 45–55 years) at a department of gynecology in Japan. Information was collected concerning age, medical history, medications, menstrual status, and history of treatment for climacteric symptoms. Oral symptoms, including xerostomia were evaluated with a 3‐point scale. The climacteric symptom checklist for Japanese women and 36‐Item Short‐Form Health were used to evaluate climacteric symptoms and QOL, respectively. In addition, the volume of unstimulated saliva, oral moisture, salivary α‐amylase, chromogranin A, and 17‐β estradiol were measured. Results: Higher age, the total number of medications, psychotropic drug, hormone replacement therapy, treatment for climacteric symptoms, sticky mouth, burning sensation of tongue, dryness of nose and 14 of the 21 climacteric symptoms significantly affected xerostomia. In addition, treatment for climacteric symptoms, fall asleep but often awake at night, headaches and dryness of nose were significantly associated with xerostomia. In conclusion, xerostomia is closely associated to factors such as treatment for climacteric symptoms and certain menopausal symptoms, and it may be related to QOL in perimenopausal women.